Comparison of the efficacy of curcumin and its nano formulation on dexamethasone-induced hepatic steatosis, dyslipidemia, and hyperglycemia in Wistar rats - Amany M. Hamed; Dalia A. Elbahy; Ahmed RH. Ahmed; Shymaa A. Thabet; Rasha Abdeen Refaei; Islam Ragab; Safaa Mohammed Elmahdy; Ahmed S. Osman; Azza MA. Abouelella (Heliyon)
Background and objective: Insulin resistance is a primary feature of type 2 diabetes. This study compared the effects of curcumin and its nanoformulation on insulin resistance, fasting blood sugar, liver function, GLUT4, lipid profile, and oxidative stress in the liver and pancreas in a diabetic model. Methods: Thirty male Wistar rats were divided into five groups: a control group, a diabetic group, a diabetic group treated with metformin (40 mg/kg), a diabetic group treated with curcumin (100 mg/kg), and a diabetic group treated with curcumin NPs (100 mg/kg). Diabetes was induced by injecting dexamethasone daily for 14 days. Treatment with curcumin and curcumin NPs was administered by gavage for 14 days. Body weight and fasting blood sugar levels were measured on days 1, 14, and 28. Results: The metformin, curcumin, and curcumin NPs groups showed significantly greater body weight gain than the untreated diabetic group (P < 0.001). In diabetic rats treated with curcumin and curcumin NPs, insulin resistance decreased by approximately 40 %, while fasting blood sugar levels dropped by 35–40 % (P < 0.001). The levels of liver enzymes (AST, ALT), cholesterol, triglycerides, LDL, and the oxidative stress marker MDA in liver and pancreatic tissues were reduced by 30–50 %. Additionally, beneficial markers such as albumin, HDL, antioxidants (GSH, SOD), and GLUT4 levels were increased by 25–45 % (P < 0.001). Nano-curcumin consistently showed greater improvements than curcumin, especially in reducing oxidative stress and supporting liver and pancreatic health. Conclusion: This study demonstrates that curcumin NPs has a superior effect on reducing oxidative stress and improving metabolic parameters in diabetes compared to curcumin. by enhancing the bioavailability and stability of curcumin, the nanoformulation showed stronger therapeutic potential for managing high blood sugar, cholesterol issues, and liver health, positioning curcumin NPs as a promising alternative to conventional treatments for diabetes and its complications.